MHD Glauert Flow Of A Hybrid Nanofluid With Heat Transfer - Waini, Iskandar; Ishak, Anuar; Pop, Ioan Mihai (Penerbit Akademia Baru, 2021)
This paper examines the wall jet flow and heat transfer of the Glauert problem with the effect of the hybrid nanoparticles. Also, the influence of the magnetic field and the variable surface temperature are taken into consideration. Here, we consider copper (Cu) and alumina (Al2O3) as the hybrid nanoparticles while water is the base fluid. The governing equations are reduced to the similarity equations using similarity transformations. Then, the numerical solutions are obtained by using the bvp4c function in MATLAB software. The findings reveal that hybrid nanofluid provides a higher heat transfer rate compared to regular nanofluid. Besides, the heat transfer rate and the skin friction coefficient increase in the presence of nanoparticles. Moreover, the rise of the temperature index parameter contributes to the enhancement of the heat transfer rate, but it does not affect the skin friction coefficient. The stronger magnetic strength led to the reduction of the heat transfer rate and the skin friction coefficient.